Pendidikan Perilaku Anak Sekolah Pada Era New Normal Di Panti Asuhan Tabah Kasih - Henny Syapitri; Novita Aryani; Edriyani Yonlafado Simanjuntak (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Background: The understanding of children in the Tabah Kasih orphanage about educating schoolchildren's behavior in the new normal era at school needs to be identified. Towards educational adaptation, each school must begin to improve itself to prepare for the implementation of education in the New Normal Era. The implementation of education in schools must be carried out directly, so it must follow strict health protocols. Objective: This Community Service increases knowledge in terms of the new normal era in the Covid 19 pandemic situation. Method: This activity uses a health promotion method with an educational approach and demonstration of the new normal era in schools. Results: The participants who took part in this activity were 32 people consisting of all child patients at the Tabah Kasih Orphanage. All (100%) participants actively participated in demonstration activities and 80% of participants expressed behavior in terms of attitudes/activities in the new normal era in school children. Conclusion: This community service activity shows that the results in the behavior of orphans apply methods/activities in new normal era situations. The results of this activity can be applied and provide knowledge to school children in new normal era situations.